2016
DOI: 10.1038/srep34937
|View full text |Cite
|
Sign up to set email alerts
|

Vectorization of biomacromolecules into cells using extracellular vesicles with enhanced internalization induced by macropinocytosis

Abstract: Extracellular vesicles (EVs, exosomes) are approximately 30- to 200-nm-long vesicles that have received increased attention due to their role in cell-to-cell communication. Although EVs are highly anticipated to be a next-generation intracellular delivery tool because of their pharmaceutical advantages, including non-immunogenicity, their cellular uptake efficacy is low because of the repulsion of EVs and negatively charged cell membranes and size limitations in endocytosis. Here, we demonstrate a methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 33 publications
7
88
0
2
Order By: Relevance
“…Detailed examinations of the physiological effects of miR-107 are needed for its safe clinical utilization. Moreover, further studies are needed on the cellular uptake or secretion systems of tumor suppressor miRNAs, leading to the development of miRNA delivery systems for future therapeutic and diagnostic applications [93][94][95][96] . These studies are currently under evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed examinations of the physiological effects of miR-107 are needed for its safe clinical utilization. Moreover, further studies are needed on the cellular uptake or secretion systems of tumor suppressor miRNAs, leading to the development of miRNA delivery systems for future therapeutic and diagnostic applications [93][94][95][96] . These studies are currently under evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Another promising therapy would be to utilize the biological functions of exosomes to deliver cancer drugs and therapies (2,(35)(36)(37)(38). For example, nanoparticle drug delivery is a rapidly burgeoning area of inquiry that capitalizes on the endogenous functions of extracellular particles by applying these to manufactured vesicles (39)(40)(41). Each of these potential therapies relies on a clear understanding of exosome internalization by recipient cells.…”
Section: Introductionmentioning
confidence: 99%
“…Macropinocytosis is not selective in which molecules are internalized from the extracellular environment, and so uptake may be dictated simply by proximity to the cells and not targeted by the exosome specifically. However, it has been shown that some exosomes naturally induce macropinocytosis internalization (64) and others, through manipulation of exosomal content, can selectively activate this mechanism increase uptake (40). Phagocytosis is a much more common method of taking up exosomes, especially with phagocytic cells of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Macropinocytosis is not selective in which molecules are internalized from the extracellular environment, and so uptake may be dictated simply by proximity to the cells and not targeted by the exosome specifically [121]. However, it has been shown that some exosomes naturally induce macropinocytosis internalization [90] and others, through manipulation of exosomal content, can selectively activate this mechanism in order to increase uptake [122]. Phagocytosis is a much more common method of taking up exosomes, especially with phagocytic cells of the immune system.…”
Section: Resultsmentioning
confidence: 99%